1995
DOI: 10.5935/0305-7518.19950014
|View full text |Cite
|
Sign up to set email alerts
|

Classification of leprosy cases under field conditions in Bangladesh. I. Usefulness of skin-smear examinations

Abstract: Summary In 2 non-governmental organization projects in Bangladesh 244 new leprosy patients were classified in the field according to clinical criteria. Skin smears were taken at 4 standardized sites and at the most active peripheral lesion, where a biopsy was also taken.Comparison of the clinical field classification with the results of the skin smears and biopsies gives a sensitivity of 92· 1 % for the clinical criteria, but a specificity of only 41'3%. The skin-smear results, on the other hand, have a sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
9
0
3
Order By: Relevance
“…Most of the misdiagnoses relating to LL disease were in the BL group and differentiating between these two types is not always straightforward. Groenen et al [19] found that adding in a category of diffuse infiltration and nodules improved the diagnosis of LL cases in the MB leprosy classification by ensuring that diffuse infiltration is not overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the misdiagnoses relating to LL disease were in the BL group and differentiating between these two types is not always straightforward. Groenen et al [19] found that adding in a category of diffuse infiltration and nodules improved the diagnosis of LL cases in the MB leprosy classification by ensuring that diffuse infiltration is not overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…14 A necessidade do exame baciloscópico para a classificação dos casos de hanseníase no campo foi avaliada em um estudo na Índia, onde os resultados demonstraram especificidade de 98,1% com a classificação baciloscópica e de 41,3% com a baseada em critérios clínicos. 15 No Brasil, Andrade e colaboradores realizaram um trabalho comparando diferentes classificações utilizadas pelas coordenações dos programas de controle em diferentes unidades da federação. Segundo esses autores, se a baciloscopia fosse o único However, although technically relatively simple and of easy accomplishment in operational terms, in most of the leprosy control programs, there were difficulties related to the implementation of the bacilloscopic exams, because they either resulted in low quality (low reproducibility or reliability), or because of the nonexistence of these exams in the public health services.…”
Section: Discussionunclassified
“…Oskam [8] reviewed previous studies [9][10][11][12][13][14], mostly prior to 1993, that compared the number of skin lesions (although not always with 15 as the cutoff) and body zones involved with skin smears or biopsies with a BI value 10-1 (table 4). The first 3 studies resulted in a low specificity (39%-42%) for a clinical diagnosis of MB leprosy in locations where MB leprosy is more common [9][10][11] but not in areas where it is less common (81%-88%) [12,13]. Misclassifying patients with PB leprosy as having MB leprosy may result in overtreatment, whereas misclassifying patients with MB leprosy as having PB leprosy may result in undertreatment.…”
Section: Methods For the Classification Of Leprosy For Treatment Purpmentioning
confidence: 99%